Build It Now : Socialism for the Twenty-First Century - Lebowitz, Michael A. (Book collections on Project MUSE., 2006)
Build It Now puts forward a clear and innovative vision of a socialist future, and at the same time shows how concrete steps can be taken to make that vision a reality. It shows how the understanding of capitalism can itself become a political act-a defense of the real needs of human beings against the ongoing advance of capitalist profit. Throughout the book, Lebowitz addresses the concerns of people engaged in struggle to create a better world, but aware that this struggle must be informed by the realities of the twenty-first century. Many chapters of the book began life as addresse.